2018
DOI: 10.1007/s00018-018-2912-y
|View full text |Cite
|
Sign up to set email alerts
|

GADD45α alleviates acetaminophen-induced hepatotoxicity by promoting AMPK activation

Abstract: As an analgesic and antipyretic drug, acetaminophen (APAP) is commonly used and known to be safe at therapeutic doses. In many countries, the overuse of APAP provokes acute liver injury and even liver failure. APAP-induced liver injury (AILI) is the most used experimental model of drug-induced liver injury (DILI). Here, we have demonstrated elevated levels of growth arrest and DNA damage-inducible 45α (GADD45α) in the livers of patients with DILI/AILI, in APAP-injured mouse livers and in APAP-treated hepatocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…AMPK has anti-inflammatory effects, regulates catabolism and anabolism, and improves the redox balance (Hayashi et al, 2000;Levine et al, 2007). The AMPK pathway is the upstream regulator of CPT1A, and it can regulate CPT1A and fatty acid β-cooxidation (Li et al, 2019). The current study demonstrated that API enhanced activation of the AMPK pathway and reversed APAP-induced hepatotoxicity.…”
Section: Metabolomic Analyses Of Cells and Serum Revealed An Aberrantsupporting
confidence: 52%
See 1 more Smart Citation
“…AMPK has anti-inflammatory effects, regulates catabolism and anabolism, and improves the redox balance (Hayashi et al, 2000;Levine et al, 2007). The AMPK pathway is the upstream regulator of CPT1A, and it can regulate CPT1A and fatty acid β-cooxidation (Li et al, 2019). The current study demonstrated that API enhanced activation of the AMPK pathway and reversed APAP-induced hepatotoxicity.…”
Section: Metabolomic Analyses Of Cells and Serum Revealed An Aberrantsupporting
confidence: 52%
“…Previous studies have demonstrated that AMP-activated protein kinase (AMPK) can activate CPT1A to protect the liver. Li et al (2019) established that the AMPK pathway was the upstream regulator of CPT1A, and it could regulate CPT1A and fatty acid β-oxidation (FAO) (Li et al, 2019). In addition, a study by Tobita et al (2018) revealed that an increase in the mRNA expression level of hepatic CPT1A was associated with Thr172 phosphorylation of AMPK α (AMPKα) in the liver, which alleviated hepatic steatosis (Tobita et al, 2018).…”
Section: Apigenin Activated Amp-activated Protein Kinase Pathway Bothmentioning
confidence: 99%
“…131 Acetaminophen-induced liver injury (AILI), a disorder characterized by hepatic metabolism dysregulation, induces a rapid increase in GADD45A levels in livers of patients and in in vivo and in vitro models, where it exerts an hepatoprotective effect. 132 For this reason, it has been suggested that Gadd45a gene expression in the liver might be used as a biomarker to identify those patients with drug-induced liver injury. 133 In particular, and within the context of AILI, GADD45A triggers AMP-activated protein kinase (AMPK) activity, a master regulator of metabolism that induces the expression of genes related to energy-producing pathways, such as glucose uptake, glycolysis, glycogenolysis, fatty acid β-oxidation, and lipolysis, while inhibiting anabolic processes, such as the gluconeogenesis and the biosynthesis of fatty acids, cholesterol, and proteins.…”
Section: Regulatory Roles Of Gadd45a In Adipose Tissue and The Livermentioning
confidence: 99%
“…All the mice were fasted overnight for approximately 12 h before the intraperitoneal (i.p.) injection of APAP (Sigma Aldrich, USA) at a dose of 750 mg/kg (body weight), 300 mg/kg (body weight), or warm saline (0.9% NaCl; 37°C), as previously described [36]. The mice were euthanized after 1, 3, 6, 12, or 24 h of treatment with APAP or saline.…”
Section: Animal Studiesmentioning
confidence: 99%